2014
DOI: 10.1002/path.4316
|View full text |Cite
|
Sign up to set email alerts
|

EMILIN2 down‐modulates the Wnt signalling pathway and suppresses breast cancer cell growth and migration

Abstract: EMILIN2 is an extracellular matrix (ECM) protein that exerts contradictory effects within the tumour microenvironment: it induces apoptosis in a number of tumour cells, but it also enhances tumour neo-angiogenesis. In this study, we describe a new mechanism by which EMILIN2 attenuates tumour cell viability. Based on sequence homology with the cysteine-rich domain (CRD) of the Frizzled receptors, we hypothesized that EMILIN2 could affect Wnt signalling activation and demonstrate direct interaction with the Wnt1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 50 publications
3
47
0
Order By: Relevance
“…Several ECM components have been shown to play a critical role, not only during its onset but also during metastasis, which is responsible for the 90% of all the cancer-related deaths [6,7,8,9,10]. In this context, the activation of proteases leads to the release of matrix fragments that act directly on cancer cells influencing their viability, apoptotic rate and/or metastatic potential [11,12,13,14,15,16]. Matrix remodeling leads also to the release of growth factors and cytokines of which the ECM represent a vital reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…Several ECM components have been shown to play a critical role, not only during its onset but also during metastasis, which is responsible for the 90% of all the cancer-related deaths [6,7,8,9,10]. In this context, the activation of proteases leads to the release of matrix fragments that act directly on cancer cells influencing their viability, apoptotic rate and/or metastatic potential [11,12,13,14,15,16]. Matrix remodeling leads also to the release of growth factors and cytokines of which the ECM represent a vital reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al observed that the overexpression of MiR-100 could inhibit the migration and invasion of breast cancer cells by transfecting miR-100 mimic in aggressive breast cancer cell lines and transfecting miR-100 inhibitor in non-metastatic cell lines. This mechanism involves MiR-100 directly inhibiting the expression of FZD-8 and inactivating the progression and reduce cell motility, impairing breast cancer cell growth and development [35]. These findings reveal a further mechanism that Emilin2 suppresses tumor growth, providing evidence of the key role of the microenvironment during tumor development and reinforcing the therapeutic potential of this molecule.…”
Section: Micrornamentioning
confidence: 70%
“…The CXXC-type zinc finger protein Cxxc5 is a pleiotropic factor that can interact with Dishevelled to inhibit Wnt/β-catenin signaling (52, 53), binds to CpG-rich DNA sequences to regulate gene expression (54), and is a biomarker and potential therapeutic target in leukemia (5557). The extracellular matrix protein Emilin2, also described as an inhibitor of Wnt signaling (58), is hypomethylated and overexpressed in AML, and is important for AML clonogenicity. Since both Cxxc5 and Emilin2 play a role in Wnt signaling and c-Myc is a target of the Wnt pathway, we monitored the level c-Myc GFP and do not find that shRNA-knockdown of either Cxxc5 or Emilin2 disrupt c-Myc accumulation (data not shown).…”
Section: Discussionmentioning
confidence: 99%